INFORMATION SECURITY RISKS INVOLVING FUNSOFT AS A HEALTH MANAGEMENT INFORMATION SYSTEM - Halwenge, Peter Migoya; Liyala, S. O; Raburu, George (IJRDO -Journal of Computer Science Engineering, 2015)
This study looked at the various information security risks brought about by the implementation of funsoft which is a health management information system with a view of managing and mitigating the risks in a coherent and systematic manner. The study has used a positivist approach with a research design that employed quantitative descriptive study of funsoft users and focus group discussions with system administrators and records officers. The study population was eighty five with a sample size of forty six calculated using Yamane’s formula with a precision of ten percent. The study reviewed current risk management practices used within the HMIS and IT in general and using a case study of three public hospitals in Kisumu county that are at different implementation levels of funsoft, it further explored current potential obstacles encountered in the implementation of systemic risk management strategy. This study finally implemented a strategy for managing risk within funsoft in a systematic and continuous manner which was enriched by material documented in the literature. It was unearthed in the study that all the three health facilities have no focal person to coordinate information security, lack policies and procedures on computer and information security and had never undertaken a risk assessment of the funsoft HMIS platform since its deployment.